Advances in Mechanics of Materials and Structural Analysis In Honor of Reinhold Kienzler (Advanced Structured Materials,, 2018)
This book presents a collection of contributions on the advanced mechanics of materials and mechanics of structures approaches, written in honor of Professor Kienzler. It covers various topics related to constitutive models for advanced materials, recent developments in mechanics of configuration forces, as well as new approaches to the efficient modeling and analysis of engineering structures. .